Pre NEET Pediatrics - Mehra Taruna; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2013)
This book has been written keeping in mind that maximum time taken to revise pediatrics is less than one day. A chapter, paediatrics in last minutes, complete summary to revise important areas in paediatrics and also to answers single liner in paediatrics. Clinical questions based on recent topics (including recent All India and AIIMS). DNB questions with authentic reference and answers.
Keywords: MCQs and Self-assessment,Pediatrics; Electronic books